Nivel de conocimiento y expectativa en contrataciones públicas en estudiantes de contabilidad de La Universidad Nacional de la Amazonía Peruana año 2023 - Soto Arevalo, Cynthia Rossana (2024)
Public procurement, crucial for the economy, relies on good management to improve public spending, stimulate the economy, and foster innovation. In Peru, the demand for certified professionals in Public Procurement has grown, seeking greater governmental efficiency. However, frequent irregularities in state purchases generate public distrust. The study aimed to determine the level of knowledge and expectations in public procurement among accounting students at the National University of the Amazonia Peruana in 2023. Using a quantitative approach and a non-experimental descriptive design, the study included a population of 97 students, applying a 20-item data collection instrument with a Cronbach's alpha reliability of 0.834. The study showed that 47% of accounting students at the National University of the Amazonia Peruana in 2023 had a high level of knowledge in public procurement, and 76% had high expectations in this area. Most have adequate normative and conceptual knowledge, but there is variability in practical experience. Students see public procurement as an opportunity to enhance job prospects, gain better remuneration, and develop a meaningful career, particularly emphasizing knowledge in regulations and processes, as well as career potential and professional recognition in this field.